Acute Warfarin Toxicity as Initial Manifestation of Metastatic Liver Disease - Varalaxmi Bhavani Nannaka; Nihar Jani; Masooma Niazi; Dmitry Lvovsky (Case Reports in Critical Care)
Near complete infiltration of the liver secondary to metastasis from the head and neck cancer is a rare occurrence. The prognosis of liver failure associated with malignant infiltration is extremely poor; the survival time of patients is extremely low. We present a case of acute warfarin toxicity as initial manifestation of metastatic liver disease. Our patient is a 64-year-old woman presenting with epigastric pain and discomfort, found to have unrecordable International Normalized Ratio. She rapidly deteriorated with acute respiratory failure requiring mechanical ventilation, profound shock requiring high dose vasopressor infusion, severe coagulopathy, worsening liver enzymes with worsening of lactic acidosis and severe metabolic abnormalities, and refractory to aggressive supportive care and died in less than 48 hours. Autopsy revealed that >90% of the liver was replaced by tumor masses.